The Effectiveness of Integrating Somatosensory Technology into Nuclear Energy Education Learning. (20th February 2015) - Huang, Yen-Ping; Wei, Hsin-Wen; Chen, Tseng-Yi; Jhang, Nai-Yuan; Chen, Chun; Cheng, Yu-Chun; Yang, Cheng-Wei; Shih, Wei-Kuan
Abstract: Introductory video games have become an attractive form of entertainment and have surpassed television viewing as a preferred sedentary activity choice for users. Introductory video games are more and more popular for users studying E-learning topics. Atomic energy is important in the fields of science education, industry and research. However, the lack of a thorough understanding of nuclear energy and radiation, and the attitudes towards the safety of nuclear power are important issues. This paper discusses the teaching of the fundamental knowledge of nuclear power to students, to enhance their understanding of including nuclear power and safety concerns. This objective was achieved by means of e-learning which contains a variety of information about general science. This plan established a Nuclear Energy 3D eBook by integrating an eBook and TV devices, using the Tsing Hua Open-pool Reactor (THOR) as an example. We employed a nuclear energy education design in a serious game. We recruited N users to participate in THOR nuclear energy education learning. The present study examines the usage pattern of electronic game devices among university students in Taiwan. A survey was conducted among 31 students in a university, with 17 males and 14 females in the age range of 19–21. The results showed students can clarify their ideas about nuclear power by using the materials. The impact of nuclear energy 3D eBook on users who learn using the 3D teaching materials was also examined.